Mental workload and occupational burnout among the faculty members and administrative staff of Yazd Public Health School - Reza Jafari Nodoushan; Farzan Madadizadeh; Vida Sadat Anoosheh; Fahima Boghri; Khalil Taherzadeh Chenani (Journal of Education and Health Promotion, 2021)
BACKGROUND: Administrative staff may be exposed to a great deal of the mental workload (MWL) due to the long working hours and the responsibility of responding to large numbers of clients. Occupational burnout (OB) is one of the issues that can be affected by MWL. The aim of the present study was to investigate the relationship between mental MWL and OB, as well as the internal interactions between OB dimensions. MATERIALS AND METHODS: This cross-sectional and descriptive (correlation) study was conducted among faculty members and administrative staff of public health school of Yazd province. Samples were collected through the simple random sampling. NASA task load index and Maslach questionnaire were used for the assessment of MWL and OB, respectively. Frequency and percentage were used for the descriptive analysis. Spearman, Mann–Whitney U, and Kruskal–Wallis H tests were used for inferential statistics. RESULTS: Ultimately, 29 individuals from faculty members and 82 individuals from administrative staff participated in this study. Most of the participants (73.9%) had experienced many MWL instances in performing their jobs duties. No significant relationship between MWL with OB and MWL with any of the demographic characteristics was found, as well (P > 0.05). In case of OB, a significant relationship was discovered between depersonalization with gender and personal accomplishment with work section (P < 0.05). CONCLUSIONS: MWL cannot be considered as a contributing factor of OB of the administrative staff because no significant relationship has been noted between them. Reducing working hours, selection of suitable staff, and allowing a few minutes to rest on a daily basis represent the suggested solutions for reducing the MWL of staff.